“Positive” urine testing for Cannabis is associated with increased risk of traffic crashes - Del Balzo, Giovanna; Gottardo, Rossella; Mengozzi, Silvia; Dorizzi, Romolo M.; Bortolotti, Federica; Appolonova, Svetlana; Tagliaro, Franco (Journal of pharmaceutical and biomedical analysis, 2018)
•The aim is verifying the association of chronic use of Cannabis with traffic crash.•% of positive urines for THC-COOH (LC–MS/MS) in traffic accidents was = 8.2.•% of positives for THC-COOH (LC–MS/MS) in a control group was = 0.8%.•Both the “chi square” test and the Odds’ ratio were highly significant (P <<< 0.01).•The usefulness of urine tests for Cannabis in driving licence issuing is confirmed. Although recent Cannabis use is widely reported to be associated with drug-related traffic accidents, the evidence that Cannabis users show an increased risk of being involved in road crashes is still not unequivocally proved. The purpose of the present work is to provide an objective assessment of this hypothesis, by comparing the frequency of occurrence of positive urine analyses in drivers involved in traffic accidents (n = 1406) with that observed in a control population undergoing mandatory urine drug testing (n = 1953). Urine analyses for drugs of abuse were performed by screening immunometric techniques followed by confirmation with UHPLC-QQQ MS, adopting a cut-off concentration for THC-COOH of 15 ng/mL. A case was classified as “positive” when a driver admitted to hospital for road traffic injuries showed urine concentrations of THC-COOH higher than the cut-off. All samples showing positive results for any other controlled drug in urine or blood alcohol concentrations >0.5 mg/mL were excluded from the study. Subjects positive to THC-COOH, and negative to all the other tested substances were 116 in Group 1 (8.2%) and 16 in Group 2 (0.8%). Subjects resulting negative to any tested substances were 1290 in Group 1 and 1937 in Group 2. The frequency of THC-COOH detection in the two groups was compared by using the “chi square” test, which resulted = 119.57, i.e. highly significant (P <<< 0.01). The Odds Ratio of the two groups was =10.88, showing a high degree of association between the presence of THC-COOH in urine and the occurrence of traffic accidents (P < 0.0001). The presented data, proving a high degree of association between Cannabis use and the occurrence of traffic accidents with injuries of the driver, support the use of urine testing for Cannabis in the procedures for the issuing of the driving licence, particularly in the case of subjects formerly or presently using Cannabis. This finding looks even more relevant in the present times, because of the increasing success of the policies of legalization of Cannabis for medical and non-medical purposes.